Cooperative learning as a method of prevention and intervention against bullying - Cano Martínez, Irene (2016)
This research proposes an educational methodology, known as cooperative learning, as a method of prevention and/or intervention against bullying. With the use of this kind of innovative learning, which involves group work and cooperation as fundamental axes, social acceptance and flexible conflicts resolution among peers increases and it also improves the school climate. Working in a cooperative way reduces the competitiveness and the individuality among peers, as well as it promotes the group cohesion and the integration of the excluded students.